Non-extensive distribution of human eye photoreceptors - Mehri, Ali (Journal of theoretical biology, 2017)
Spatial distribution of cone and rod photoreceptors in human eye retina, are studied by using non-extensive statistics. We show that photoreceptors’ packing density obeys q-exponential and q-Gaussian distributions. Cones retinal distribution has higher non-extensivity in young subjects in comparison with old ones. Absolute value of q-parameter for spatial distribution of both types of photocells gets higher values along horizontal meridian. We also calculate Shannon's additive entropy and Tsallis’ non-additive entropy for cone photocells distribution in retina, and compare their results. Information entropy, especially Tsallis entropy, is capable to discriminate between young and old subjects, properly. Our results confirm the ability of non-extensive statistics to unveil retinal eye problems caused by abnormal photoreceptors distribution. •We evaluate distribution of human eye photoreceptors, by non-extensive statistics.•q-deformed functions properly describe packing density of cone and rod photocells.•Non-extensivity of cones is higher for young subjects in comparison with old ones.•Absolute q-parameter along horizontal meridian is greater than vertical meridian.•Tsallis entropy discriminates between olds and youngs better than Shannon entropy.